Cut off value in prediction of success in triathlon mixed relay - Ledanois, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The mixed team triathlon relay first occured in the program of the Olympic Games in Tokyo 2021. National teams of 4 triathletes compete with every athlete running the super sprint distance (300 m swim, 7km cycle and 1,5 km run) in the Women / Men / Women / Men order. Until now, only one conference paper enlight this event (Pöller, 2015) on one event race. Recent developments on WTCS relays increase the number of events and offers the possibility to analyze more races. To determine which placements along the race lead to the podium, we investigated athletes time on every sequence of the races. As a result, it helps staffs optimizing the composition of their relay.